(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The Government of India proposed the New Education Policy (NEP) 2020, which was a surprising and timely step among the global difficulties caused by the COVID-19 epidemic. Educationists were taken aback by the unexpected scope and magnitude of the planned reforms in the NEP 2020. This research study examines the notable consequences of NEP 2020 on higher education, providing a comprehensive examination of its prominent characteristics and their influence on the current education system. This research primarily examines the impact of the policy on higher education, but it has also brought significant changes to school and college education. The NEP 2020 includes innovative modifications, including the reorganisation of the undergraduate programme, the encouragement of interdisciplinary education, and the incorporation of vocational training into higher education. Furthermore, the strategy places strong emphasis on the integration of technology into education, a change that has been expedited by the epidemic. This study intends to evaluate the possible impact of NEP 2020 on higher education in India by examining the proposed reforms. It will analyse how these reforms may bring about significant changes in the present system and identify any obstacles that may arise during their implementation. This research provides insights into the future of higher education in India by examining policy papers, current literature, and empirical data related to NEP 2020.